Orang Ambon dan Perubahan Kebudayaan - Jacob Ajawaila (Antropologi Indonesia, 2000)
The Ambonese is a community that underwent changes from time to time as a result of the influence of religion, government's policies and global culture. The changes have further implications. A considerable 'in group' solidarity of village as totality (supported by villagers and their special rights, excluding the newcomers) became segregated because of religion. Religion has taken over the traditional rites. The village as an entity of traditional laws based upon genealogy has undergone changes into a public village. The village has become multi profiled with its activities based on needs, e.g. the ceremonial needs for the benefits of traditions. Traditional institutions that strengthened social relations between villages have weakened as a result of the government's policies, and so is the traditional institutions that fulfill the needs of the traditional community.